Associations of positive orientation with health and psychosocial adaptation: A review of findings and perspectives. Issue 2 (19th June 2018) - Caprara, Gian Vittorio; Alessandri, Guido; Caprara, Mariagiovanna
Abstract : Earlier findings have shown that positive evaluations about oneself, life, and future are related to each other and can be traced to a common latent dimension originally named positive orientation and then positivity . Further findings have led to the development of an eight‐item scale that allows a direct measurement of positivity. A review is presented of the major findings that point to positivity as a basic self‐evaluative disposition and that attest to its relevant impact across domains of functioning. Finally, possible avenues for promoting positivity and to allow individuals to fully benefit from it are discussed.